Perspektif pedagogik tentang evaluasi pendidikan: Analisis kesiapan guru dalam penerapan kurikulum se-kabupaten Rokan Hulu (kurikulum 2013 versus kurikulum merdeka) - Sohibun; Setiawan, Agus; Samsudin, Achmad; Yustika, Yusi Riksa (Karoteh Utama, 2023)
This research aims to provide a basis, reference, and insights into teachers' readiness in considering the implementation of two different curricula, namely the Merdeka Curriculum (KM) and the 2013 Curriculum (K13), while also describing teachers' perceptions of both curricula. This article serves as a valuable source of information for teachers by offering a comprehensive view and information regarding curriculum implementation. The method used in writing this article involves qualitative and descriptive literature studies. Data were obtained through literature reviews and observations, supplemented by structured interviews with several teachers from elementary, junior high, and senior high schools in Rokan Hulu Regency selected purposively. Upon reevaluation, it was found that more teachers in Rokan Hulu tend to support the Merdeka Curriculum based on the existing KM system. However, it was also found that in Rokan Hulu, using the K-13 Curriculum is more efficient, considering teacher competencies and the availability of adequate school facilities, which only partially support the seamless implementation of the KM. As stated,